2020
DOI: 10.1128/aem.00760-20
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for the Selection of Plant Growth-Promoting Rhizobacteria Based on Bacterial Competence Mechanisms

Abstract: ABSTRACT The use of plant growth-promoting rhizobacteria (PGPR) is increasingly meaningful for the development of more environmentally friendly agricultural practices. However, often the PGPR strains selected in the laboratory fail to confer the expected beneficial effects when evaluated in plant experiments. Insufficient rhizosphere colonization is pointed out as one of the causes. With the aim of minimizing this inconsistency, we propose that besides studying plant growth pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 52 publications
(95 reference statements)
0
25
0
2
Order By: Relevance
“…Isolates that looked promising in the laboratory often fail to deliver in pot or field trials (Chauhan et al ., 2015). The major factors that adversely affect bacterial efficiency in the field are (i) the soil physicochemical properties of farmlands, which differ largely from laboratory trials; (ii) the bacterial inability to colonize the plant rhizosphere, resulting in the lack of so‐called rhizosphere competence (Bach et al ., 2016; Amaya‐Gómez et al ., 2020); (iii) and the strict mutual dependencies and competition in the rhizobiome (Benizri et al ., 2001; Schink, 2002; Barea et al ., 2005; Babalola, 2010; de Souza et al ., 2015; Backer et al ., 2018). The rationale behind this current study is that the rhizosphere environment is not included in the in vitro screenings for PSB, while the plant–bacteria interactions are paramount in securing effective plant growth‐promoting traits (Schloss and Handelsman, 2005; Bais et al ., 2006; Lebeis et al ., 2012; Stewart, 2012; Castrillo et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Isolates that looked promising in the laboratory often fail to deliver in pot or field trials (Chauhan et al ., 2015). The major factors that adversely affect bacterial efficiency in the field are (i) the soil physicochemical properties of farmlands, which differ largely from laboratory trials; (ii) the bacterial inability to colonize the plant rhizosphere, resulting in the lack of so‐called rhizosphere competence (Bach et al ., 2016; Amaya‐Gómez et al ., 2020); (iii) and the strict mutual dependencies and competition in the rhizobiome (Benizri et al ., 2001; Schink, 2002; Barea et al ., 2005; Babalola, 2010; de Souza et al ., 2015; Backer et al ., 2018). The rationale behind this current study is that the rhizosphere environment is not included in the in vitro screenings for PSB, while the plant–bacteria interactions are paramount in securing effective plant growth‐promoting traits (Schloss and Handelsman, 2005; Bais et al ., 2006; Lebeis et al ., 2012; Stewart, 2012; Castrillo et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Strain performance was compared with those of two promising PGPB, RHFS10, and RHFS18 strains, belonging to the Bacillus genus and isolated from J. sabina rhizosphere of the same collection site ( Castaldi et al, 2021 ) and proposed as biocontrol agents for their antagonistic activity against the phytopathogen M. phaseolina . Most of the new strains displayed root-colonization phenotypes since able to surface spread by swarming and to form biofilms ( Amaya-Gómez et al, 2020 ), while only five were found either positive to both solubilization of phosphate, indoleacetic acid (IAA), and siderophore production. Strains RHF6, RHF15, and RHFB showed a better performance than when compared against the already characterized rhizobacteria strains RHFS10 and RHFS18, confirming that the microenvironments created under or nearby nurse shrubs are a promising source of PGPB ( Rodríguez-Echeverría et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to gaining understanding of gvg cluster regulation, the impact of FVG production on the transcriptome, and the regulation of FVG production by acidic amino acids, we observed that genes necessary for rhizocompetence phenotypes were positively regulated in the absence (or decrease) of FVG. There are several well-documented competence traits common to rhizosphere-colonizing bacteria [ 51 , 52 , 53 , 54 , 55 ]. Motility in Pf is important for root colonization [ 56 ] and highly motile variants have a competitive advantage [ 57 ].…”
Section: Discussionmentioning
confidence: 99%